2016
DOI: 10.1007/jhep11(2016)181
|View full text |Cite
|
Sign up to set email alerts
|

Second stop and sbottom searches with a stealth stop

Abstract: Abstract:The top squarks (stops) may be the most wanted particles after the Higgs boson discovery. The searches for the lightest stop have put strong constraints on its mass. However, there is still a search gap in the low mass region if the spectrum of the stop and the lightest neutralino is compressed. In that case, it may be easier to look for the second stop since naturalness requires both stops to be close to the weak scale. The current experimental searches for the second stop are based on the simplified… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 129 publications
(158 reference statements)
0
10
0
Order By: Relevance
“…In this case, searching for the asymmetric decay chains with one sbottom decaying tot W , the other decaying to tχ ± or bχ 2 could be useful. For larger values of the stop-neutralino mass gap, the stop decay products become more visible and it might be useful to look at channels with multiple b-jets or multiple leptons [56], or try to tag the charm quark from stop decay [23][24][25]. On the other hand, if the mass gap is smaller, the stop decay could exhibit displaced vertex, which can help reduce SM background in both the mono-jet search and the search with sbottom decays.…”
Section: Jhep04(2017)084mentioning
confidence: 99%
“…In this case, searching for the asymmetric decay chains with one sbottom decaying tot W , the other decaying to tχ ± or bχ 2 could be useful. For larger values of the stop-neutralino mass gap, the stop decay products become more visible and it might be useful to look at channels with multiple b-jets or multiple leptons [56], or try to tag the charm quark from stop decay [23][24][25]. On the other hand, if the mass gap is smaller, the stop decay could exhibit displaced vertex, which can help reduce SM background in both the mono-jet search and the search with sbottom decays.…”
Section: Jhep04(2017)084mentioning
confidence: 99%
“…Moreover, comparing to the method in Ref. [44,46] which utilise the leptons and b-jets in the final state, our search strategy can achieve a few times larger signal significance because of higher signal rate.…”
Section: B Signal and Background Analysismentioning
confidence: 97%
“…Moreover, one would expect two bottom quark jets in the final state if the flavor changing decay oft 1 → cχ 0 1 is suppressed. Studies [40,41,43,44,46] have shown that searching for final states with leptons and b-jets provides as a good probe to the light stop sector, especially when mt 1 ∼ m t +mχ0 1 . However, for some of our benchmark points, e.g.…”
Section: A Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…This attitude is supported by the flurry of theoretical activity in recent years in designing models which "hide" the new physics from the LHC. One of the standard methods for doing so is to arrange for a "compressed" mass spectrum with a mass degeneracy of the relevant particles, such as supersymmetric (SUSY) partners, so that the resulting decay products are too soft to be triggered upon and tagged in the experimental analysis [4][5][6][7][8][9][10][11][12][13], or a "stealth" mass spectrum, where the new physics signature becomes identical to the SM background, since the additional particles are too soft to make any appreciable difference [14][15][16][17][18][19][20]. Our aim will be to highlight a kinematic variable that, either by itself or in conjunction with more conventional variables, can more effectively select signal over background when the signal spectrum is compressed and when signal events contain multi-stage cascade decays.…”
Section: Introductionmentioning
confidence: 99%